(untitled) (REVISTA NODO, 2025)
In this article, I will present the Manifesto of Anti-Modern Art (published in digital version in https://www. motorhueso.net/wuwei/manifiesto-del-arte-anti- moderno/), written in 2024 in the midst of the unbridled and seemingly unstoppable rise of generative artificial intelligence and its growing impact on various artistic fields. I will also offer a series of follow- up comments intended to contextualize the manifesto and detail some of the ideas and experiences that influenced its writing.